PENGARUH LATIHAN PASSING BERPASANGAN TERHADAP PASSING BAWAH BOLA VOLI EKSTRAKULIKULER DI SMP NEGERI 1 PAJAR BULAN - Falyandra, Revino; Disurya, Ramanata; Akhbar, M.Taheri (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study was motivated by the low underhand passing ability of students participating in the volleyball extracurricular program at SMP Negeri 1 Pajar Bulan. The purpose of this study was to determine the effect of paired passing exercises on students’ underhand passing skills in volleyball. The research employed an experimental method using a One Group Pretest-Posttest Design. The population consisted of all students participating in the volleyball extracurricular program, while the sample comprised 18 students selected through purposive sampling. Data were collected using an underhand passing skill test. The data were analyzed using a paired sample t-test with the assistance of SPSS version 26. The results showed that paired passing exercises had a significant effect on improving students’ underhand passing skills. This was indicated by a significance value of 0.000, which was lower than 0.05 (0.000 < 0.05), leading to the rejection of H0 and acceptance of Ha. Therefore, paired passing exercises are effective in improving the underhand passing ability of volleyball extracurricular students at SMP Negeri 1 Pajar Bulan.